A Study on The Availability of ICT at Secondary Level in Secondary Schools of Kottayam District In Kerala, India - Elizabeth S., Kuriakose (INTI International University, 2023)
Today is an era of educational revolution globally. In order to bring about tremendous changes in the educational sector, technologies especially, information and communication technologies (ICTs) play a pivotal role. The shifting paradigms in the educational system necessitated the call for the use of ICT in schools. ICT has the potential to address the innumerable needs of students and also teachers, as it demonstrated its power by entering into virtual reality which is a computer-stimulated environment that can simulate physical presences in places in the real as well as imaginary world and this is a manifestation of knowledge revolution. The proposed study intends to look in to the availability of ICT in schools of Kottayam district in Kerala, INDIA . The findings of the study are of immense use to school heads, teachers, students as well as parents and thereby to the society as a whole.